Laptop use and its antecedents among educators : a review of the literature. - Moses, Priscilla; Md Khambari, Mas Nida; Wong, Su Luan (EuroJournals, Inc, 2008)
The rapid growth of Information and Communication Technology (ICT) has enabled the creation of mobile technology that can be used to enhance the instructional process. One of the recent mobile devices introduced in classroom instruction is the laptop. Indeed, schools around the globe are using laptops for educational purposes with increasing frequency. Based on a review of the literature, this paper explores how educators use the laptop. It then explores the antecedents of laptop use among the educators.